Behavioral Interest in Purchasing Halal Products: Exploring an Extended Theory of Planned Behavior Effect - Najmudin; Ahyakudin (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Indonesia has a large Muslim population reaching 209.1 million people or around 13.1 percent of the world's Muslim population, with the millennial generation as the largest generation, reaching 34 percent of Indonesia's population, in terms of buying behavior, the millennial generation is the subject of this study, they have a wishy-washy buying behavior, more likely to see the brand than see the halal label, so that sales of products not labeled halal are higher than products labeled halal. This study aims to determine the effect of attitude, perceived controlled behavior, subjective norms, and trust on the purchase intention behavior of halal products. The method used in this research is quantitative, with a population of millennial people in Banten Province who have consumed halal products, with a sample of 170 respondents, and the data collection technique using a questionnaire. The data was processed using Smart PLS 3.2.9 software and analyzed using the structural equation modeling (SEM) method with a partial least square (PLS) approach. The results of this study indicate that attitude and perceived controlled behavior have a significant positive effect on the purchase intention behavior of halal products, while subjective norms and trust have no effect on the purchase intention behavior of halal products. The implication of this research is that the marketing strategy for halal products must focus on increasing positive attitudes and perceived controlled behavior of consumers. Efforts to build strong brands and facilitate access to halal products are more important than relying on subjective norms and trust. Marketing policies and campaigns should emphasize personal benefits and ease of obtaining halal products to increase purchase intention among consumers.